2021
DOI: 10.1016/j.tra.2020.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Mobility as a service and private car use: Evidence from the Sydney MaaS trial

Abstract: Australia's first Mobility as a Service (MaaS) trial commenced in April 2019 in Sydney, running for two years. The objective of the trial is at least twofold -to assess interest in various MaaS subscription plans through bundling public transport, rideshare, car share and car rental with varying financial discounts and monthly subscription fees, in contrast to pay as you go (PAYG); and to assess the extent to which the use of the private car might change following a subscription to a monthly mobility bundle. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 23 publications
(9 reference statements)
1
37
0
Order By: Relevance
“…We note that all the MaaS trials reviewed by Hensher et al [6] entailed a relatively advanced level of integration of transport services, which included booking and payment. In a more recent study focusing specifically on the Sydney MaaS trial, MaaS was found to reduce car use [7]. These findings contrast with those of a MaaS pilot study in Belgium, which found no drastic reduction in car use, and concluded that MaaS can act as a complement rather than a substitute of the car [30].…”
Section: Maas and Sustainable Mobilitymentioning
confidence: 73%
See 1 more Smart Citation
“…We note that all the MaaS trials reviewed by Hensher et al [6] entailed a relatively advanced level of integration of transport services, which included booking and payment. In a more recent study focusing specifically on the Sydney MaaS trial, MaaS was found to reduce car use [7]. These findings contrast with those of a MaaS pilot study in Belgium, which found no drastic reduction in car use, and concluded that MaaS can act as a complement rather than a substitute of the car [30].…”
Section: Maas and Sustainable Mobilitymentioning
confidence: 73%
“…Public transport should be the backbone of any sustainable transport system [4]. Some limited, small-scale MaaS trials show some reduction in private car use, and an increase in car sharing and/or public transport use [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The correct design of a MaaS offer concerning these factors is of utmost importance as they can potentially impact how a MaaS offer is used and its potential to decrease private car ownership. First evidence supports the claim that MaaS could decrease private car usage (Hensher et al, 2021); however, due to a lack of substantial behavioural data, it remains unclear how these design decisions influence the perception and the impact of MaaS and to what degree and how MaaS can change travel behaviour (e.g., mode choice, car ownership).…”
Section: Maas Key Challengesmentioning
confidence: 82%
“…Against this evidence is the rather more encouraging evidence from trials that underpins our fourth key issue. The experience with subscription plans and discounts in the Sydney trial (Hensher et al 2021) suggests that there is the potential to gain subscribers and reduce private car use, but there is little in a business model to turn this into a profitable activity. The Sydney Trial demonstrated the potential of selling MaaS as a monthly or periodic bundle, with or without non-mobility services, suggesting MaaS products (cf.…”
mentioning
confidence: 99%